Biometric and metabolic profiles associated to different rearing conditions in offshore farmed gilthead sea bream (Sparus aurata L.). Issue 11 (13th April 2014) - Melis, Riccardo; Anedda, Roberto; Cifuentes, Alejandro
<x xml:space="preserve">Abstract</x> Modern multivariate methods are applied to both biometric measurements and NMR metabolic profiling of fillet to discriminate farmed gilthead sea bream reared in different farming conditions. Two fish groups having the same average size, from the same farm, were caught in May and October. Biometric data demonstrate that condition factor is higher for the leaner fish, sampled in May, while liver somatic index is lower in fish sampled in October. Biometric features are related to metabolic changes that involve lipid storage from May to September, and their mobilization from muscle and liver during prespawning season (September, October). Structural phospholipids (phosphatidylcholine, phosphatidylethanolamine) and essential fatty acids (eicosapentaenoic and docosahexaenoic acids) characterize the lipid profile of the May catch, while triglycerides, monounsaturated and diunsaturated fatty acids, likely from absorption of vegetable oil components of feeds, suggest fish fattening in the warm season and discriminate fish caught in October. Among polar metabolites, taurine, glutamine, glycine, alanine, and creatine/phosphocreatine confirm their role as good biomarkers for the discrimination among fish produced in different farming conditions, especially involving feed digestion and metabolism, chronic stress, and alteration of energetic balance in cage‐reared fish. Qualitative traits of farmed fish are therefore the result of a complex combination of environmental factors and farming practices, which should be analyzed to increase consumers' and farmers' awareness.